2021
DOI: 10.18103/mra.v9i11.2600
|View full text |Cite
|
Sign up to set email alerts
|

The Return on Investment from Rapid DNA Testing of Sexual Assault Kits

Abstract: The growing queue for DNA analysis in crime laboratories has prevented the analysis from providing investigative leads as turnaround time has grown, limiting the analytical results to a confirmatory role in the courtroom. Rapid DNA technology offers an opportunity to employ an automated system for the development of a DNA profile. The Rapid DNA technology permits a police booking station to take a buccal swab obtained from an arrestee, acquire a DNA profile, and test that profile against a DNA database, all wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Overall, this developmental validation provides strong support for the use and further exploration of Rapid DNA methods for processing a wide variety of casework samples, including sample types that are commonly collected during sexual assault investigations. Furthermore, the Kentucky State Police conducted a pilot study in 2019 that tested casework sexual assault samples with the ANDE Rapid DNA system, making Kentucky the first state in the U.S. to use a Rapid DNA approach to generate successful investigative leads in sexual assault cases [64,94]. The authors reported saving 261 days in turnaround time with Rapid DNA testing, as well as a minimal cost difference of ~$500 more compared to the laboratory’s cost for their traditional testing of a sexual assault kit [64].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, this developmental validation provides strong support for the use and further exploration of Rapid DNA methods for processing a wide variety of casework samples, including sample types that are commonly collected during sexual assault investigations. Furthermore, the Kentucky State Police conducted a pilot study in 2019 that tested casework sexual assault samples with the ANDE Rapid DNA system, making Kentucky the first state in the U.S. to use a Rapid DNA approach to generate successful investigative leads in sexual assault cases [64,94]. The authors reported saving 261 days in turnaround time with Rapid DNA testing, as well as a minimal cost difference of ~$500 more compared to the laboratory’s cost for their traditional testing of a sexual assault kit [64].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the Kentucky State Police conducted a pilot study in 2019 that tested casework sexual assault samples with the ANDE Rapid DNA system, making Kentucky the first state in the U.S. to use a Rapid DNA approach to generate successful investigative leads in sexual assault cases [64,94]. The authors reported saving 261 days in turnaround time with Rapid DNA testing, as well as a minimal cost difference of ~$500 more compared to the laboratory’s cost for their traditional testing of a sexual assault kit [64]. A forensic laboratory in Singapore has also reported success in generating leads for a variety of urgent casework samples using GlobalFiler Express chemistry on a RapidHIT 200 [61].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technology Working Group produced white papers on several new technologies and continues to assess emerging technology questions (NIJ Forensic Laboratory Needs Technology Working Group (FLN-TWG), 2021a, 2021b, 2021c, 2021d). Elsewhere, return on investment reviews of new technology inform the industry of the economic value of new technologies [ 68 ].…”
Section: Business Strategymentioning
confidence: 99%